Pengaruh Perawatan Metode Kanguru Terhadap Fungsi Fisiologis Bayi Prematur Dan Kepercayaan Diri Ibu Dalam Merawat Bayi - Syamsu, Andi Fatmawati (Jurusan Keperawatan FIKES UNSOED, 2013)
Premature babies at risk of death 70 times higher than term infants. Approximately one-fifth of premature infants can not survive in the first year, Maintenance kangaroo method is one effective treatment for premature babies. The purpose of this study to determine the effect of kangaroo care method to physiological responses of premature infants and mothers' confidence in caring for the baby. The study design was a one group pre and post test. Sampling by purposive sampling amounted to 14 respondents. Data analysis using the Wilcoxon test and paired difference test. Hasi statistical tests showed no significant differences in the physiological responses of premature infants and mothers confidence in caring for the baby. Kangaroo method can be a routine action to improve the physiological responses in hospitals and hospital Undata Anutapura Palu. The hospital set up a special room to maintain the privacy of the patient.